2021
DOI: 10.1111/ans.17404
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in Far North Queensland: a new take on an old story

Abstract: Background Appendicitis is a leading cause of surgical hospital admission. To date, there have been no published epidemiological studies describing appendicitis in tropical and remote Australia and none specifically documenting appendicitis in Indigenous Australians. This descriptive study used available state data to investigate appendicitis across Far North Queensland (FNQ). Methods Queensland Health hospital admission data for FNQ was analysed to explore appendicitis epidemiology and outcomes in FNQ, 2012–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…In one epidemiological study, it was demonstrated that Indigenous patients with appendicitis had higher ICU admission rates and longer inpatient stays compared to non-Indigenous patients. 15 However, the study was purely descriptive and did not examine how differences in socioeconomic status and distance from hospital between the two groups could account for this disparity. Increased distance from hospital was shown to increase the length of stay for both Indigenous and non-Indigenous patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one epidemiological study, it was demonstrated that Indigenous patients with appendicitis had higher ICU admission rates and longer inpatient stays compared to non-Indigenous patients. 15 However, the study was purely descriptive and did not examine how differences in socioeconomic status and distance from hospital between the two groups could account for this disparity. Increased distance from hospital was shown to increase the length of stay for both Indigenous and non-Indigenous patients.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which socioeconomic status and distance from hospital play a role in this disparity is unclear. In one epidemiological study, it was demonstrated that Indigenous patients with appendicitis had higher ICU admission rates and longer inpatient stays compared to non‐Indigenous patients 15 . However, the study was purely descriptive and did not examine how differences in socioeconomic status and distance from hospital between the two groups could account for this disparity.…”
Section: Introductionmentioning
confidence: 99%
“…55 Furthermore, both appendicectomy and paediatric surgical outcomes in rural northern Australia were equivalent to national outcomes. 56,57 Two retrospective studies reported no significant difference in post-operative pancreaticoduodenectomy or gastrectomy mortality in rural compared with metropolitan centres, despite only 7.4% of pancreaticoduodenectomies and 3.8% of gastrectomies being done rurally. 58,59 In Townsville, after introduction of a specialised hepatobiliary unit, there were no Narrative reviews significant differences in operative approach or complexity, nor in mortality or complication rates between the two periods (ie, before and after the specialised hepatobiliary service).…”
Section: Patient Outcomesmentioning
confidence: 99%
“…A 2018 study explored mortality after emergency abdominal surgery in a cohort of 237 patients over five years in Mount Gambier (RA2) and found that emergency laparotomy mortality rates were better than published international rates 55 . Furthermore, both appendicectomy and paediatric surgical outcomes in rural northern Australia were equivalent to national outcomes 56,57 …”
Section: Patient Outcomesmentioning
confidence: 99%